Physician practice style for mental health conditions: The case of ADHD - Kelli Marquardt (Federal Reserve Bank of Chicago, 2022)
There is a robust literature documenting the importance of physician practice style (e.g., the propensity to perform certain operations) in explaining outcomes related to patients' physical health. Yet little is known about the role of physicians in explaining patients' mental health outcomes. This paper uses novel data on doctor note text together with natural language processing techniques to estimate and document heterogeneity in physician practice style for diagnosing Attention Deficit Hyperactivity Disorder (ADHD). I find significant variation in both diagnostic intensity (the mean propensity to diagnose) and diagnostic compliance (the weight that physicians place on medical guidelines). Physician characteristics can explain some of this heterogeneity. Specifically, both female physicians and recent graduates have higher diagnostic compliance and lower diagnostic intensity than their respective counterparts. Mental health diagnostic errors lead to excess medical and societal spending. Given the costs of such errors, the findings in this paper encourage a re-evaluation of the mental health identification process, though perhaps targeted at specific sub-groups of physicians.
Keywords: I10; J24; C8; 330; Physician Practice Style; Child Mental Health; Textual Analysis